The optimal true ileal digestible lysine requirement for nursery pigs between 27 to 44 lb - James, B.W.; Hastad, C.W.; Lawrence, K.R.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 20-d growth assay was conducted to determine the appropriate true ileal digestible lysine requirement to maximize growth performance of pigs between 27 to 44 lb. The basal diet (1.0% true ileal digestible lysine; 20.1% CP) was corn-soybean meal-based and was formulated to contain 3% added fat. Sand was substituted with L-lysine⋅HCl to form the other treatment diets (1.1, 1.2, 1.3, and 1.4% true ileal digestible lysine). The positive control contained more soybean meal than the basal diet (44.2 vs. 32.2% of the diet) and no L-lysine⋅HCl to provide 1.3% true ileal digestible lysine. Growth performance improved (quadratic, P<0.04) with increasing true ileal digestible lysine and was maximized at 1.1% true ileal digestible lysine. Feed efficiency was better (quadratic, P<0.01) for pigs fed increasing true ileal digestible lysine and was best for pigs fed 1.3% true ileal digestible lysine. These results indicate that the true ileal digestible lysine requirement for the 27 to 44 lb pig is at least 1.1% for ADG and 1.3% for feed efficiency.
Keywords: Lysine; Growth performance; Nursery pigs; Swine